Effect of seasonality on the quality of bovine oocytes selected by the brilliant cresyl blue method - Maia, Roger C.; Mogollón Waltero, Edgar M.; Dubeibe Marin, Diego F.; Pena Carvalho, Bruno; Burla Dias, Ángelo J. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: The brilliant cresyl blue (BCB) staining is a non-invasive test to select the best-suited oocytes for embryonic development. This makes it a useful tool to select best-quality oocytes at the times of the year when there is forage restriction. Objective: To evaluate the effect of seasonality on the nuclear maturation and quality of oocytes selected by the BCB test. Methods: The cumulus-oophorus complexes (COCs) were obtained in summer and winter of 2010 and 2011. Selected COCs were maintained for 90 min at 38.5 °C in a CO2 incubator, in TCM 199 medium containing 10% fetal bovine serum and antibiotics, and supplemented with 26 μM brilliant cresyl blue. Afterwards, they were divided according to the ooplasm staining (BCB+ —blue; BCB− —unstained). Subsequently, COCs were matured for 22 h. Nuclear maturation was evaluated at 22 h of culture. Results: The proportion of BCB− oocytes was higher in the winter of 2010, but there was no increase in this group in the winter of 2011. The percentage of oocytes that reached metaphase II was higher in control and BCB+ groups in relation to oocytes from BCB− group. Conclusion: The season of the year influences the percentage of oocytes best suited for embryonic production in situations in which oocyte donors receive pasture-based feeding, since the method was effective in determining the effect of seasonality on the competence of bovine oocytes to reach nuclear maturation.